Effect of kenaf fiber in reinforced concrete slab - Sharifah Maszura, Syed Mohsin; Jokhio, Gul Ahmed; Baarimah, A. O. (IOP Publishing Ltd, 2018)
The effect of kenaf fibers in reinforced concrete slab with different thickness is discusses and presented in this paper. Kenaf fiber is a type of natural fiber and is added in the reinforced concrete slab to improve the structure strength and ductility. For this study, three types of mixtures were prepared with fiber volume fraction of 0%, 1% and 2%, respectively. The design compressive strength considered was 20 MPa. Six cubes were prepared to be tested at 7th and 28th day. A total of six reinforced concrete slab with two variances of thickness were also prepared and tested under four-point bending test. The differences in the thickness is to study the potential of kenaf fiber to serve as part of shear reinforcement in reinforced concrete slab that was design to fail in shear. It was observed that, addition of kenaf fiber in reinforced concrete slab improves the flexural strength and ductility of the reinforced concrete slab. In the slab with reduction in thickness, the mode of failure change from brittle to ductile with the inclusion of kenaf fiber.